Dietary BCAAs (Branched Chain Amino Acids) and Cognitive Function: Implications for Nutritional Interventions in Elderly Populations - Willya Eka Putri; Nur Indrawaty Lipoeto; Roza Mulyana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The aging process is often accompanied by a decline in cognitive function, impacting memory, attention, and decision-making. Malnutrition, including protein deficiency, is recognized as a contributing factor to cognitive decline in elderly populations. Branched-chain amino acids (BCAAs), essential amino acids obtained solely from dietary sources, play a pivotal role in various physiological processes, including neurotransmitter synthesis and protein synthesis in the brain. This study aims to investigate the relationship between serum BCAA levels and cognitive function in elderly individuals. Methods: A cross-sectional study was conducted on 25 elderly subjects (age > 60 years) in Padang, Indonesia. Serum BCAA levels were measured using High-Performance Liquid Chromatography (HPLC), and cognitive function was assessed using the Montreal Cognitive Assessment - Indonesian version (MoCA-Ina). Statistical analysis was performed to determine the correlation between BCAA levels and MoCA-Ina scores. Results: The mean serum levels of total BCAAs, leucine, isoleucine, and valine in the elderly subjects were 0.40 ± 0.15 mM, 0.09 ± 0.06 mM, 0.05 ± 0.02 mM, and 0.26 ± 0.10 mM, respectively. The median MoCA-Ina score was 23 (range: 8-27), indicating a significant proportion of participants with cognitive impairment. Statistical analysis revealed no significant correlation between total BCAA levels and MoCA-Ina scores (r = 0.071, p = 0.735). However, a moderate positive correlation was observed between isoleucine levels and MoCA-Ina scores (r = 0.344, p = 0.092), although not statistically significant. Conclusion: This study suggests that serum BCAA levels, particularly isoleucine, may have implications for cognitive function in elderly populations. Further research with a larger sample size and longitudinal design is warranted to elucidate the complex relationship between dietary BCAAs, serum BCAA levels, and cognitive health in aging individuals.